Factors Influencing Marital Satisfaction in The First Five Years of Marriage: A Systematic Literature Review - Ludya Nurfirdausa; Kartika Sari Dewi (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Marital satisfaction during the first five years of marriage is a vital indicator of relationship stability, as couples face major adjustments in this early phase. This study uses a Systematic Literature Review (SLR) based on PRISMA guidelines to explore factors influencing early marital satisfaction or newlyweds satisfaction. Articles were sourced from Google Scholar, PubMed, and ScienceDirect, resulting in 264 identified records. After screening, 10 empirical studies published between 2020 and 2024 were included. Findings indicate that communication quality is the most consistent predictor of marital satisfaction, encompassing emotional dialogue, conflict resolution, financial discussion, and sexual expression. Additionally, sexual satisfaction, emotional self regulation, authenticity, and assertiveness support marital adjustment and stability. These traits foster empathy and mutual respect, especially under early marital stressors. In conclusion, strong interpersonal communication and psychological readiness are essential for sustaining relationship quality. These insights underscore the need for communication focused education in premarital and early marital interventions.